Engineering energy aluminum conductor composite core (ACCC) and its application - Chen, Yuan (Elsevier and CEPP energy series., 2019)
Engineering Energy Aluminum Conductor Composite Core (ACCC) and its Application discusses this group of aluminum fibers that are characterized by their lightweight, high tensile strength, large current-carrying capacity, high temperature resistance, corrosion resistance, and small, linear expansion coefficient which make the ACCC of carbon fiber the most promising new conductor species. With the development of this technology and the reduction in product price, the ACCC of carbon fiber can play an important role in power grid construction and upgrading. The book contains a large number of practical engineering application examples and problems found in practical operation and maintenance. It is an ideal reference, providing theoretical and practical support for those in electrical engineering, aluminum conductors and overhead transmission lines.